Intermintten Fasting : Keterkaitannya dalam Kesehatan dan Islam - Najwa Saffa Ameera Fatoni; Amanda Kayla Putri; Nasywa Khalda Naura (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Intermittent fasting (IF) is a popular dietary method for weight control and metabolic health. In addition to weight loss, IF has also been investigated as a method of blood sugar control, particularly for individuals with type 2 diabetes or prediabetes. In a religious contet, fasting has been part of the spiritual practices of Muslims for centuries, with mandatory fasting during the month of Ramadan as one of the pillars of Islam. This article will discuss how intermittent fasting scientifically plays a role in blood sugar control and how this concept of fasting correlates with Islamic teachings.